2014
DOI: 10.2340/16501977-1853
|View full text |Cite
|
Sign up to set email alerts
|

Goal attainment following upper-limb botulinum toxin-A injections: Are we facilitating achievement of client-centred goals?

Abstract: Goal setting and review provides a clinically useful process for measuring upper-limb botulinum toxin-A outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
3
18
0
3
Order By: Relevance
“…In the case of post-stroke patients, it is significant to carry out objective assessment of the state of a paretic hand, including the intensity of spasticity and the level of motor control. These factors lead to the deterioration of limb function and disability [3][4][5]. In their research, Keng et al revealed that 3 months post stroke, spasticity occurred in 33% of the patients [6].…”
Section: Streszczeniementioning
confidence: 99%
See 3 more Smart Citations
“…In the case of post-stroke patients, it is significant to carry out objective assessment of the state of a paretic hand, including the intensity of spasticity and the level of motor control. These factors lead to the deterioration of limb function and disability [3][4][5]. In their research, Keng et al revealed that 3 months post stroke, spasticity occurred in 33% of the patients [6].…”
Section: Streszczeniementioning
confidence: 99%
“…Czynniki te prowadzą do pogorszenia funkcji ręki i niepełnosprawności [3][4][5]. W badaniu Keng i wsp.…”
Section: Wstępunclassified
See 2 more Smart Citations
“…This would be beneficial in establishing the correlation between GAS and the severity of spasticity. 9,10 In summary, irrespective of what condition they have, patients prefer selecting goals in the activities and participation domain; however, it is important that therapists have the expertise to negotiate mutual, realistic, and achievable goals based on a patient's motor recovery level. In some patients, achieving impairmentbased goals will maintain the affected joint and muscle structure so that if active movement returns, patients will be able to function.…”
mentioning
confidence: 99%